Improved tissue sections for medical liver biopsies: a comparison of 16 vs 18 g biopsy needles using digital pathology. Issue 5 (19th December 2013) - Palmer, Timothy; Georgiades, Izabela; Treanor, Darren; Wright, Alexander; Shah, Mushtaq; Khosla, Randeep; Wyatt, Judith I
Abstract : Background: Most medical liver biopsies in the UK are now taken in radiology departments using 18 g biopsy needles. Subjectively, the resulting biopsies are narrow and fragile. Aim: To compare the quality of liver biopsy tissue sections obtained from 16 and 18 g biopsy needles. Method: Fifty consecutive routine medical liver biopsies obtained with 16 and 18 g needles, processed identically in the same laboratory, were measured using digital pathology software. We recorded their fragmentation, length, width, area and number of portal tracts. Results: Biopsies obtained with 16 g needles more often resulted in an intact core in tissue sections than those with 18 g needles (71% vs 24%, p<0.001) and were significantly wider (average width of tissue 0.88 vs 0.53 mm, p<0.001). The average total area of tissue per pass was 11.38 mm 2 compared with 8.34 mm 2 (p<0.001). The number of complete portal tracts per length of biopsy was very variable, but double for 16 vs 18 g biopsies. Routinely taking two passes with the 18 g needle compensated for the reduced area, but the resulting liver in tissue sections was fragmented and distorted. Conclusions: Our results support the routine use of 16 g rather than 18 g biopsy needles for routine ultrasound-guided medical liver biopsies. A second pass should be considered if the first biopsy core is short, especially for investigation of disease stage.